Reverse lateral upper arm flaps for treating large soft tissue defects extending from the elbow to the forearm. Issue 1 (31st December 2022) - Okamoto, Hideki; Kawaguchi, Yohei; Miwa, Shinji; Aiba, Hisaki; Senda, Hiroya; Murakami, Satona; Hayakawa, Kazuo; Joyo, Yuji; Murakami, Hideki; Kimura, Hiroaki
Abstract: In this study, we report three cases wherein reverse lateral upper arm flaps were used to treat very large tissue defects extending from the elbow to the forearm. The flap sizes were 19 × 6.5 cm, 20 × 7 cm, and 17 × 7 cm. All flaps survived and elbow motion recovered sufficiently.